2020
DOI: 10.3386/w26960
|View full text |Cite
|
Sign up to set email alerts
|

International Trade and Social Connectedness

Abstract: We use anonymized data from Facebook to construct a new measure of the pairwise social connectedness between 180 countries and 332 European regions. We find that two countries trade more with each other when they are more socially connected and when they share social connections with a similar set of other countries. The social connections that determine trade in each product are those between the regions where the product is produced in the exporting country and those where it is used in the importing country… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In previous work, we have shown that this measure predicts a large number of important economic and social interactions. For example, social connectedness as measured through Facebook friendship links is strongly related to patterns of sub-national and international trade (Bailey et al, 2020b), patent citations (Bailey et al, 2018b), and investment decisions (Kuchler et al, 2020). More generally, we have found that information on individuals' Facebook friendship links can help understand their product adoption decisions and their housing and mortgage choices (Bailey et al, 2018a(Bailey et al, , 2019a.…”
Section: Data Descriptionmentioning
confidence: 73%
“…In previous work, we have shown that this measure predicts a large number of important economic and social interactions. For example, social connectedness as measured through Facebook friendship links is strongly related to patterns of sub-national and international trade (Bailey et al, 2020b), patent citations (Bailey et al, 2018b), and investment decisions (Kuchler et al, 2020). More generally, we have found that information on individuals' Facebook friendship links can help understand their product adoption decisions and their housing and mortgage choices (Bailey et al, 2018a(Bailey et al, , 2019a.…”
Section: Data Descriptionmentioning
confidence: 73%
“…Facebook networks therefore resemble real-world social networks more closely than networks on other online platforms where uni-directional links to non-acquaintances (e.g., celebrities) are common. Indeed, a number of prior studies show that Facebook networks predict many important real-world economic and social interactions including patterns of trade (Bailey et al, 2020a), patent citations (Bailey et al, 2018b), travel flows (Bailey et al, 2019b(Bailey et al, , 2020b, bank lending (Rehbein et al, 2020), social program participation (Wilson, 2019), investment decisions , and disease transmission . Information on individuals' Facebook friendship links can also help understand their product adoption decisions (Bailey et al, 2019c) and their housing choices (Bailey et al, 2018a(Bailey et al, , 2019a.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…We also documented that it predicts a large number of important economic and social interactions. For example, social connectedness as measured through Facebook friendship links is strongly related to patterns of sub-national and international trade [6], patent citations [3], travel flows [5], investment decisions [13] and the spread of COVID-19 [14]. More generally, we have found that information on individuals' Facebook friendship links can help understand their product adoption decisions [7] and their housing and mortgage choices [2,4].…”
Section: Datamentioning
confidence: 70%